Respuesta :
Answer:
The answer to your question is y = -2x + 11
Step-by-step explanation:
A (1, 9)
B (3, 5)
- Find the slope
[tex]m = \frac{y2 - y1}{x2 - x1}[/tex]
[tex]m = \frac{5 - 9}{3 - 1}[/tex]
[tex]m = \frac{-4}{2}[/tex]
m = - 2
- Find the line equation
y - y1 = m (x - x1)
y - 5 = -2(x - 3)
y - 5 = -2x + 6
y = -2x + 6 + 5
y = -2x + 11
Answer: y=-2x+11
Find the slope by: y1-y2/x1-x2
Plug in the number so
9-5/1-3 = 4/-2 =-2
So the slope is -2
Y=-2x+b
9=-2(1) +b
9=-2+b
b=11
Answer:Y=-2x+11
Find the slope by: y1-y2/x1-x2
Plug in the number so
9-5/1-3 = 4/-2 =-2
So the slope is -2
Y=-2x+b
9=-2(1) +b
9=-2+b
b=11
Answer:Y=-2x+11